2019
DOI: 10.1017/s0007114519000643
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns modify the association between fat mass and obesity-associated genetic variants and changes in obesity phenotypes

Abstract: The present study investigated whether dietary patterns could interact with fat mass and obesity-associated (FTO) polymorphisms in relation to changes in BMI and waist circumference (WC) over 3⋅6 years of follow-up. Subjects were selected from participants of the Tehran Lipid and Glucose Study (n 4292, 43⋅2 % male). Dietary data were collected using a valid and reliable FFQ. Dietary patterns were determined using factor analysis. The genotypes of polymorphisms (rs1421085, rs1121980, rs17817449, rs8050136, rs99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
0
18
1
Order By: Relevance
“…Conducted research on genetic background does not prove a significant effect of genetic mutations on the frequency of MONW occurrence [27]. Hosseini-Esfahani et al proved that the occurrence of rs17817449 is associated with an increased BMI and WC, however, it can be modified by changing dietary patterns [28]. In our study we found no association between increased WC and the investigated polymorphism.…”
Section: Discussioncontrasting
confidence: 63%
“…Conducted research on genetic background does not prove a significant effect of genetic mutations on the frequency of MONW occurrence [27]. Hosseini-Esfahani et al proved that the occurrence of rs17817449 is associated with an increased BMI and WC, however, it can be modified by changing dietary patterns [28]. In our study we found no association between increased WC and the investigated polymorphism.…”
Section: Discussioncontrasting
confidence: 63%
“…Increased consumption of western-style foods, such as fast foods and soft drinks, was associated with a prominent BMI increase in subjects with higher GRS, compared to subjects with lower GRS (P-value for interaction = 0.01). The interaction between the GRS and western-style food consumption was significant for waist size changes (P-value for interaction < 0.05) 38 .…”
Section: Discussionmentioning
confidence: 93%
“…At the same time, no signi cant association was detected between those SNPs and metabolically healthy obesity [29]. Another study was designed to investigate the interaction between dietary patterns and FTO polymorphisms regarding changes in BMI and WC over 3⋅6 years of followup [30]. Six common SNPs (rs1421085, rs1121980, rs17817449, rs8050136, rs9939973, and rs3751812) within the FTO gene region were chosen.…”
Section: Resultsmentioning
confidence: 99%